Winning the war for talent in emerging markets : - Hewlett, Sylvia Ann (Harvard Business Review Press, 2011)
Drawing on groundbreaking research, amplified with on-the-ground examples from companies as diverse as Google, Infosys, Goldman Sachs, and Siemens, this book is required reading for all companies seeking to strengthen their talent pipeline in these rich and expanding markets.